2013
DOI: 10.1016/j.epsl.2013.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Cosmogenic nuclide enhancement via deposition from long-period comets as a test of the Younger Dryas impact hypothesis

Abstract: We explore the idea that detectable excursions in 26 Al may arise from direct deposition by any bolide, and excursions in 14 C and 10 Be abundances in the atmosphere may result from long-period comet impacts. This is very different from the usual processes of production by cosmic rays within Earth's atmosphere. Long-period comets experience greatly increased cosmic ray flux beyond the protection of the sun's magnetic field. We report the computed amount of 14 C, 10 Be, and 26 Al present on long-period comets a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…They also note that their measurements are coeval with sightings of a comet and dust event documented in ancient Chinese chronicles. However, it was concluded in other studies that the dimensions needed for a comet to account for this additional injection of radiocarbon would need to be significantly more massive2829 than the previous estimates16. In consequence, the comet would inevitably have had a considerable and observable impact on the geobiosphere.…”
Section: Resultsmentioning
confidence: 93%
“…They also note that their measurements are coeval with sightings of a comet and dust event documented in ancient Chinese chronicles. However, it was concluded in other studies that the dimensions needed for a comet to account for this additional injection of radiocarbon would need to be significantly more massive2829 than the previous estimates16. In consequence, the comet would inevitably have had a considerable and observable impact on the geobiosphere.…”
Section: Resultsmentioning
confidence: 93%
“…Comas are known to have percent levels of nitrogen by weight (in the forms of NH 3 , NH 2 , NH, etc) 21 22 , and are heavily exposed, as compared to nitrogen within the earth's atmosphere because of lacking a magnetic field protection 23 . Considering that meteorite usually has 14 C and 10 Be about two orders of magnitude higher than those of rocks from the Earth's surface 24 25 26 , it is reasonable to propose that coma and comet may be expected to have 14 C/ 12 C ratios several orders of magnitude higher than that of the Earth's atmosphere 23 . Generally, 14 C occurs in very low concentrations in the Earth's atmosphere, i.e., no more than one part per trillion of the total carbon content of the atmosphere 27 .…”
Section: Discussionmentioning
confidence: 99%
“…), it is not directly associated with the Schwabe solar cycle, which only produces atmospheric radiocarbon changes of 3-4‰ over an average of 11 years [Stuiver and Braziunas, 1993;Baroni et al, 2011]. [Overholt and Melott, 2013;Usoskin and Kovaltsov, 2014;Chapman et al, 2014]. Subsequently, Allen [2012] argued in favor of a supernova explosion, but since no remnant of such an explosion has been observed, it is not considered a very likely source of the cosmic ray events [Miyake et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [2014] suggested a cometary impact on the Earth's atmosphere as the explanation of the first cosmic ray event, but this is considered unlikely due to the size of the comet required to produce the amount of excess radiocarbon and an erroneous interpretation of a historical text describing a comet in 773 C.E. [Overholt and Melott, 2013;Usoskin and Kovaltsov, 2014;Chapman et al, 2014]. Other proposed explanations include a cometary impact on the Sun [Eichler and Mordecai, 2012] and a gamma ray burst (GRB) [Hambaryan and Neuhäuser, 2013;Pavlov et al, 2013], but such sources are now considered less likely, in part because the 775 C.E.…”
Section: Introductionmentioning
confidence: 99%